The Implementation of Dictation (Tingxie) in Chinese Online Learning for Beginner-Level Students - Nanda Lailatul Qadriani (Universitas Al Azhar Indonesia, 2023)
Dictation (tīngxiě) is commonly applied to evaluate students' ability to master Chinese characters. However, dictation is challenging to use in online learning because lecturers do not have full control over the conditions around students when dictation is carried out. Students tend to think more about a